Effect of Two Frequencies of Whole-Body Vibration Training on Balance and Flexibility of the Elderly: A Randomized Controlled Trial. (October 2016) - Tseng, Shiuan-Yu; Hsu, Pi-Shan; Lai, Chung-Liang; Liao, Wan-Chun; Lee, Meng-Chih; Wang, Chun-Hou
ABSTRACT: Objective: The aim of this study was to investigate the effects of whole-body vibration training with different frequencies on the balance and flexibility of the healthy elderly. Design: The participants were recruited from hospital volunteers and the community; all of them were healthy subjects, all over 65 years of age. The study involved three randomized groups in a parallel and single-blind design. The main outcome variables included the limits of stability test and the sit and reach test, which were measured at pre-training, Month 1 (Mid-training), Month 3 (Post-training), and Month 6 (Follow-up). Results: A total of 45 subjects, with a mean age of 69.6 ± 3.9 years, were randomly divided into three groups. There was significant interaction in the performance of the limits of stability and sit and reach tests in the different groups at the four different time points (F = 25.218, P < 0.001, F = 12.235, P < 0.001, respectively). There was a significant difference in balance performance between the vibration groups at the frequencies of 20 Hz and 40 Hz and the control group at Month 1, Month 3, and Month 6 ( P < 0.001). Conclusion: Whole-body vibration training at 20 Hz has significant benefit to the balance and flexibility of the elderly who do not engage in habitual exercise. Abstract : Supplemental digital content is available in the text.